"The knife needs the intention of the heart" The construction of ethnic and moral boundaries in Israeli slaughterhouses. (February 2023) - Ben-Yonatan, Anat
This study examines aspects of ethnic, religious, and moral boundary work among Jewish-Israeli kosher slaughterers based, on 35 in-depth interviews, four ethnographic observations, informal conversations, and other secondary sources such as video footage of the slaughter sites gathered between 2014 and 2019. In Israel, the self-proclaimed sovereign homeland of the Jewish people, being Jewish means being part of the political, ethnic, and religious hegemony. While being stigmatized for doing dirty work, the Jewish slaughterers' workplace setting groups them with menial laborers from a minority ethnic group, both physically and organizationally. The stigma associated with animal killing in Israel encourages the slaughterers to distinguish themselves from other workers by engaging in boundary work. Within the workplace setting, this boundary work occurs around various aspects of intersecting identities: racio-ethnic, national, religious, and professional. Furthermore, this boundary work is fueled by various organizational mechanisms such as the slaughter site's spatial architecture, differential wage structure, and the use of tools and technologies. While these workplace conditions are determined by the employers, they are constantly restructured and reinforced by the slaughterers to assert their moral superiority vis-a-vis other workers. While exploring these organizational mechanisms, I conceptualize the Jewish slaughter knife as a boundary-maintaining object . I claim that the slaughterers constantly leverage these material, symbolic, and discursive resources to morally segregate the two workers' groups and the morally tainted aspects of slaughter, such as violence and cruelty, to the 'Arab' others. Meanwhile, the prevailing Jew–Arab tensions and the popular symbolic representation of the Arabs ensures that these behaviors are treated as an inherent racio-ethnic trait, thereby reinforcing these boundaries.